Growth and yield of corn under surface and subsurface drip irrigation - Conde, José; Sánchez-Urdaneta, Adriana; Colmenares, Ciolys; Ramiro, Edison; Ortega-Alcalá, Jorge (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2022)
To evaluate the effect of surface and subsurface drip irrigation on the growth and yield of corn, a trial was carried out at the Technical University of Machala-Ecuador, 1,600 m2 of hybrid corn (PIONEER 30K75) were cultivated to apply the treatments: irrigation by surface and subsurface drip at 10, 20 and 30 cm depth. The seed was sown in August 2019 at 80 cm between rows and 40 cm between plants, two seeds per point, with a plant density of 62,500 plants.ha-1. The experimental design was randomized blocks with four treatments and four repetitions. Plant height, fresh and dry biomass of leaves, stalks, and roots, biomass of 100 dry kernels, and yield of dry kernel were evaluated. The highest plant height and biomass of 100 dry kernels was 2.79 m, and 39.08 g, which corresponded to the subsurface drip irrigation treatment at a depth of 30 cm; the highest fresh and dry biomass of leaves, 13,631.3 kg.ha-1 and 3,800 kg.ha-1 respectively, as well as the highest yield of dry kernel 10,337.5 kg.ha-1 was for the subsurface drip irrigation treatment at 20 cm depth. The highest fresh and dry biomass of stalks 32,768.8 kg.ha-1 and 10,381.3 kg.ha-1, and the fresh and dry biomass of roots of 6,381.3 kg.ha-1 and 2,150 kg.ha-1, corresponded to the superficial drip irrigation treatment. With drip irrigation, at 20 and 30 cm depth, higher growth and yield were obtained.